Comparative cytogenetics in Astyanax (Characiformes: Characidae) with focus on the cytotaxonomy of the group - Tenorio, Renata Cristina Claudino De Oliveira; Vitorino, Carla De Andrade; Souza, Issakar Lima; Oliveira, Claudio; Venere, Paulo Cesar (Sociedade Brasileira de Ictiologia, 2013)
Astyanax é um grupo bastante diverso de peixes neotropicais cujas diferentes formas ocupam distintos ambientes. Esta grande variabilidade também se reflete em aspectos citogenéticos e moleculares, que têm sido repetidamente demonstrados por meio de estudos citogenéticos. A fim de caracterizar o cariótipo de representantes deste gênero, seis espécies foram estudadas: Astyanax altiparanae, A. elachylepis, A. xavante, A. argyrimarginatus e duas espécies novas provisoriamente citadas como Astyanax sp. e A. aff. bimaculatus. Um estudo citogenético detalhado com base na coloração convencional com Giemsa, AgNORs, banda C, fluorocromos base-específicos, e FISH com sondas para genes ribossomais 18S e 5S foi realizado com o objetivo de compreender alguns dos mecanismos cromossômicos associados com a alta diversificação que caracteriza este grupo de peixes e que culminou com o estabelecimento dessas espécies. Os resultados revelaram 2n = 50 cromossomos para cinco espécies e 2n = 52 cromossomos para Astyanax sp. Pequenas variações na macroestrutura dos cariótipos foram identificadas e se mostraram relevantes quando analisadas com base nos bandamentos clássicos, coloração por fluorocromos base-específicos e FISH com sondas de DNA 18S e 5S. Esssa diversidade cariotípica detectada indica a necessidade de uma revisão taxonômica no grupo de indivíduos aqui referidos como A. aff. bimaculatus, inclusive com a descrição de Astyanax sp., incluindo a possibilidade de inserção dessa unidade em outro gênero distinto de Astyanax.

Astyanax is a diverse group of Neotropical fishes, whose different forms occupy different environments. This great diversity is also reflected on cytogenetic aspects and molecular markers, which have repeatedly been demonstrated by cytogenetic studies. In order to characterize the karyotype of species of this genus, six species were studied: Astyanax altiparanae, A.argyrimarginatus, A. elachylepis, A. xavante, and two new species provisionally called Astyanax sp. and A. aff. bimaculatus. A detailed cytogenetic study based on conventional staining with Giemsa, AgNORs, C-banding, base-specific fluorochromes, and FISH using ribosomal genes 18S and 5S was conducted, aiming to understand some of the chromosomal mechanisms associated with the high diversification that characterizes this group and culminated with the establishment of these species. The results showed 2n = 50 chromosomes for five species and a karyotype with 52 chromosomes in Astyanax sp. Small variations in the macrostructure of the karyotypes were identified, which were quite relevant when analyzed by classical banding, fluorochromes, and FISH methods. These differences among Astyanax spp. (2n = 50) are largely due to changes in the amount and types of heterochromatic blocks. Astyanax sp (2n = 52), in addition to variations due to heterochromatic blocks, has its origin possibly by events of centric fission in a pair of chromosomes followed by minor rearrangements.These results show an interesting karyotypic diversity in Astyanax and indicate the need of a review of the group referred as A. aff. bimaculatus and the description of Astyanax sp., including the possibility of inclusion of this unit in another genus.
Keywords: C-banding; CMA3 and DAPI fluorochromes; Fish chromosome; rDNA genes; NORs